Screening method for platform conductor integrity assessment for life extension prioritisation - Ramasamy, Ramesh; Ibrahim, Zainah; Chai, Hwa Kian (Elsevier, 2018)
Most of the major oilfields in the North Sea, Persian Gulf and South China Sea are becoming very mature, with their assets exceeding their calculated design life. Severe corrosions on the metallic structures of oil wells consisting of the conductor and casings, combined with spalling of annular cement forming the barriers can result in catastrophic events leading to structural collapse and wellhead vertically dropping onto the platform deck. With the collected inspection records, a systematic approach is deemed essential to assess the in-place condition of these wells and to categorise them for life extension works. This paper presents a simplified screening method for the structural integrity assessment of platform conductors towards the end of their design life and the prioritisation which follows thereafter for life extension operations by bridging the gap between design data and inspection records. The deterministic and probabilistic integrated approach is taken to address this problem, by considering the information collected from the as-built design records to the in-place inspections, coupled with the operating and metocean loads. The pragmatic and novel conductor operating guideline curves are proposed and constructed to present the evaluated integrity states, which will enable operators to rapidly categorise conductors for rehabilitation. This screening method is applied to a group of 40-year old water injection wells, and is demonstrated to have the practical prospect, and can be automated to provide a robust and effective assessment technique.